Reforms of the pre-graduate curriculum for medical students: the Bologna process and beyond (Swiss Medical Weekly, 2012)
For several years, all five medical faculties of Switzerland have embarked on a reform of their training curricula for two reasons: first, according to a new federal act issued in 2006 by the administration of the confederation, faculties needed to meet international standards in terms of content and pedagogic approaches; second, all Swiss universities and thus all medical faculties had to adapt the structure of their curriculum to the frame and principles which govern the Bologna process. This process is the result of the Bologna Declaration http://www.bologna-bergen2005.no/Docs/00-Main_doc/990719BOLOGNA_DECLARATION.PDF of June 1999 which proposes and requires a series of reforms to make European Higher Education more compatible and comparable, more competitive and more attractive for Europeans students. The present paper reviews some of the results achieved in the field, focusing on several issues such as the shortage of physicians and primary care practitioners, the importance of public health, community medicine and medical humanities, and the implementation of new training approaches including e-learning and simulation. In the future, faculties should work on several specific challenges such as: students’ mobility, the improvement of students’ autonomy and critical thinking as well as their generic and specific skills and finally a reflection on how to improve the attractiveness of the academic career, for physicians of both sexes.